THE INFLUENCE OF DIRECT TEACHING MODELS ON THE LEARNING OUTCOMES OF GRADE VIII STUDENTS AT MTs AL-FALAHIYAH NANGA STUDY YEAR 2019/2020 - Amalia Siyanti Mafira; Adrianus Nasar; An Nisaa Al Mu'min Liu (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This study aims to study the effect of the direct instruction model on class VIII student learning outcomes at MTs Al-Falahiya Nanga Academic Year 2019/2020. This type of research is a quantitive research survey and the design used is Ex-Post Facto. The population in this study was class VIII MTs Al-Falahiyah Nanga and the study sample was obtained by 38 people obtained by simple random sampling technique. The data obtained is the value of student learning outcomes. The data analysis technique used is the Kolmogorov Smirnov test for the normality test as a prerequisite test for analysis and one-sample test for the hypothesis test. The results of the analysis of the data obtained generated a significant model of direct instruction on student learning outcomes. This conclusion is based on the results of hypothesis testing on learning outcomes. The results obtained are the standard deviation = 5,521 with the number of students 38 people and df = 37 at a significant level of 0,000 and obtained = 14,514 at the significant level of the table sig (2-tailed) 0,05 then rejected and accepted.